ANALISIS KATA AFIKSASI DALAM LIRIK LAGU POP BALI BERJUDUL “SATYA” KARYA DEK ULIK - Ni Putu Gadis Pustika Sari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This study aims at describing the use of affixation in the lyrics of the Balinese pop song entitled